Structural and functional properties and digital image texture analysis of gelatin, pectin, and carrageenan gels with honey addition - Varela, María Soledad (2023)
Gels combined with honey might generate new possibilities of textures in food development. This work explores the structural and functional properties of gelatin (5 g/100 g), pectin (1 g/100 g), and carrageenan (1 g/100 g) gels with different content of honey (0–50 g/100 g). Honey decreased the transparency of gels and made them more yellow-greenish; all of them were firm and uniform, especially at the highest honey content. The water holding capacity increased (63.30–97.90 g/100 g) and moisture content, water activity (0.987–0.884) and syneresis (36.03–1.30 g/100 g) decreased with the addition of honey. This ingredient modified mainly the textural parameters of gelatin (Hardness: 0.82–1.35 N) and carrageenan gels (Hardness: 2.46–2.81 N), whereas only the adhesiveness and the liquid like-behavior were increased in the pectin gels. Honey increased the solid behavior of gelatin gels (G': 54.64–173.37 Pa) but did not modify the rheological parameters of the carrageenan ones. Honey also had a smoothing effect on the microstructure of gels as observed in the scanning electron microscopy micrographs. This effect was also confirmed by the results of the gray level co-occurrence matrix and fractal model's analysis (fractal dimension: 1.797–1.527; lacunarity: 1.687–0.322). The principal component and cluster analysis classified samples by the hydrocolloid used, except the gelatin gel with the highest content of honey, which was differentiated as a separate group. Honey modified the texture, rheology, and microstructure of gels indicating that it is possible to generate new products to be used in other food matrices as texturizers.